Urogenital dysfunction and quality of life in women after stroke: Pilot study (Journal of Health Sciences, 2022)
Introduction: Research shows that urinary and sexual dysfunction is very common neurological sequelae of stroke with a markedly significant impact on body self-image and quality of life. Still, there is a lack of recent research to address this problem in female stroke survivors. The study aimed to examine the existence and level of urinary and sexual dysfunction, quality of life, and self-reported body image in a group of women after stroke and compare findings with those found in a group of women with other chronic non-neurological diseases.Methods: This study’s sample consisted of 30 females; two groups composed of 15. The stroke group consisted of subjects after stroke and the non-neurological group with different chronic non-neurological, mainly muscle-skeletal conditions. This study’s specific interest data were collected from respondents through pelvic floor distress inventory (PFDI-20), the pelvic floor impact questionnaire (PFIQ-7), female sexual function index (FSFI), and an eight-item body image scale (BIS). The SPSS v.26 program was used for statistical processing.Results: Results show a statistically higher scores in stroke group (M = 219.65 ± 34.573) on PFDI-20 than in non-neurological group (M = 118.54 ± 27.734). Furthermore, statistically significant higher scores were found in stroke group in PFIQ-7 (Mdn = 233.33) and BIS (Mdn = 16.00) than in non- neurological group (Mdn = 28.57) – PFIQ-7; (Mdn = 11.00) – BIS. Also, statistically significant lower scores were found in stroke group (Mdn=10.40) on FSFI index than in non-neurological group (Mdn=24.60).Conclusions: Women after stroke show significantly more urinary and sexual dysfunction, lower quality of life, and poorer body self-image than the non-neurological group of chronic non-neurological conditions. There is a clear need for research on this issue in women after stroke.